PENGARUH PENERAPAN LATIHAN IMAGERY TERHADAP HASIL TEMBAKAN PADA JARAK 30 METER EKSTRAKURIKULER OLAHRAGA PANAHAN SMP NEGERI 02 BAKUNG BLITAR - SULTON MANAZI, MOCHAMAD (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract An archer must have motion mechanism or basic technique, mentality and physical health. In the process of training, students often find the difficulty to maintain the basic archery technique, so the change of the technique will result the different range. For that, the effort to maintain students’ basic technique is needed in order to overcome the problem faced during the shooting and to improve the result of shooting. The purpose of this study is to know the effect of imagery exercise toward the shot at a distance 30 meters in extracurricular archery. The research was conducted at SMPN 02 Bakung Blitar. The data is taken from samples consists of 27 students of SMPN 02 Bakung Blitar who follow the extracurricular archery and using non-probabiliti sampling. The data calculation is using paired sample t test. The data calculation result of pre test mean is 74.37, the standard deviation is 9.27, the post test mean is 81, and the standard deviation of post test is 10.74. thus it can be concluded there is on improvement. So, the application of imagery exercise affects on the shot at a distance of 30 meters in extracurricular archery at SMPN 02 Bakung Blitar with an increase of 8,9%. Keywords: Archery, Imagery Exercise, Shots Results.